2017
DOI: 10.2217/lmt-2017-0004
|View full text |Cite
|
Sign up to set email alerts
|

The Route to Diagnosis: Emergency Presentation of Lung Cancer

Abstract: r Emergency presentation (EP) of cancer can be defined as the diagnosis of a new cancer as part of attending an emergency service such as Accident and Emergency, the Emergency Department or an Acute Medical Unit. r EP is common in lung cancer, affecting up to 40% of new diagnoses, and is a feature of healthcare in all countries. r EP of lung cancer is associated with specific patient demographics, such as older age and more co-morbidities, and certain disease characteristics including more advanced stage of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…[13][14][15][16] A study by Newsom-Davis et al reported that African Americans were more likely to present through the Emergency Department and that EP patients with lung cancer had a fourfold higher risk of dying within the first month of diagnosis versus their outpatient counterparts even when standardizing for age, stage, and histological subtype. 16 A subset analysis of our own URM population similarly found that the increase in the proportion of EP diagnoses was largely driven by the Black population. In addition to diagnosis location, it has been reported that delays in diagnosis of pancreatic cancer can lead to a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] A study by Newsom-Davis et al reported that African Americans were more likely to present through the Emergency Department and that EP patients with lung cancer had a fourfold higher risk of dying within the first month of diagnosis versus their outpatient counterparts even when standardizing for age, stage, and histological subtype. 16 A subset analysis of our own URM population similarly found that the increase in the proportion of EP diagnoses was largely driven by the Black population. In addition to diagnosis location, it has been reported that delays in diagnosis of pancreatic cancer can lead to a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients diagnosed with cancer in the emergency department have an increased mortality. 13 16 A study by Newsom-Davis et al reported that African Americans were more likely to present through the Emergency Department and that EP patients with lung cancer had a fourfold higher risk of dying within the first month of diagnosis versus their outpatient counterparts even when standardizing for age, stage, and histological subtype. 16 A subset analysis of our own URM population similarly found that the increase in the proportion of EP diagnoses was largely driven by the Black population.…”
Section: Discussionmentioning
confidence: 99%